The effects of individual market orientation, personality, emotional intelligence and commitment on banks' employee performance - Abdallah Ally Sendaro, 1976-, author; Rohaizat Baharun, supervisor; Fakulti Pengurusan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Ph.D (Pengurusan)) - Universiti Teknologi Malaysia, 2018